2020
DOI: 10.5194/acp-2020-778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biodegradation by bacteria in clouds: An underestimated sink for some organics in the atmospheric multiphase system

Abstract: Abstract. Water-soluble organic compounds represent a significant fraction of total atmospheric carbon. The main oxidants towards them in the gas and aqueous phases are OH and NO3 radicals. In addition to chemical solutes, a great variety of microorganisms (e.g. bacteria, viruses, fungi) has been identified in cloud water. Previous lab studies suggested that for some organics, biodegradation by bacteria in water is comparable to their loss by chemical processes. We perform model sensitivity studies over large … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Accordingly, we found that along with genes associated with the biodegradation of organic contaminants, methane metabolism genes were also positively correlated with PM 10 concentration, as well as genes associated with glyoxylate and dicarboxylate metabolism, which includes formate metabolism. All or some of these substances might be relevant to metabolic activity in the atmosphere due to their biodegradation, as suggested in other studies, 65,78 as well as in dust-affected terrestrial and marine regions.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Accordingly, we found that along with genes associated with the biodegradation of organic contaminants, methane metabolism genes were also positively correlated with PM 10 concentration, as well as genes associated with glyoxylate and dicarboxylate metabolism, which includes formate metabolism. All or some of these substances might be relevant to metabolic activity in the atmosphere due to their biodegradation, as suggested in other studies, 65,78 as well as in dust-affected terrestrial and marine regions.…”
Section: Discussionsupporting
confidence: 57%
“…Recent evidence on the possible metabolic activity of bacteria in the atmosphere suggests that speci c carbon sources are likely to sustain bacteria, e.g., formate, acetic acid and ethanol. 8,65,78 Moreover, it was suggested that bacterial metabolism might also affect cloud or even atmospheric chemistry. 65,102 Our results suggest that if dust storms carry viable bacteria, they may be metabolically relevant for atmospheric chemical cycles and may spread these bacteria globally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major unknown is what proportion of the marine aerobiota is metabolically active and whether this has a significant effect on aerosol-cloud interactions and the processing of marine DOM in the atmosphere. Cloud water contains DOM, which could support microbial metabolism (Khaled et al, 2020), including the remineralization of DOM back to carbon dioxide. Ervens and Amato (2020) estimated that the global loss of DOM in clouds is 0.008-0.011 Pg C yr −1 , which is insignificant when compared with the 662 Pg C as DOM in the ocean (Hansell et al, 2009), or estimates of annual oceanic photosynthetic production of 45-55 Pg C yr −1 (Longhurst et al, 1995;Field et al, 1998;Carr et al, 2006;Westberry et al, 2008).…”
Section: Ecological Significance Of Marine Microorganisms In the Atmospherementioning
confidence: 99%